Recent Advances in Maize Nuclear Proteomic Studies Reveal Histone Modifications - Casati, Paula (Frontiers in Plant Science, 2012)
The nucleus of eukaryotic organisms is highly dynamic and complex, containing different types of macromolecules including DNA, RNA, and a wide range of proteins. Novel proteomic applications have led to a better overall determination of nucleus protein content. Although nuclear plant proteomics is only at the initial phase, several studies have been reported and are summarized in this review using different plants species, such as Arabidopsis thaliana, rice, cowpea, onion, garden cress, and barrel clover. These include the description of the total nuclear or phospho-proteome (i.e. Arabidopsis, cowpea, onion), or the analysis of the differential nuclear proteome under different growth environments (i.e. Arabidopsis, rice, cowpea, onion, garden cress and barrel clover). However, only few reports exist on the analysis of the maize nuclear proteome or its changes under various conditions. This review will present recent data on the study of the nuclear maize proteome, including the analysis of changes in posttranslational modifications in histone proteins.